The effects of sliding parameters on dry wear characteristics of Ti-6Al-4V alloy - Mohammed , Baba Ndaliman; Bala, Katsina Christopher; Khan, Ahsan Ali; Mohammad , Yeakub Ali; Abdullahi, Umma; Abdulmumin , Adebisi Adetayo (Trans Tech Publications, Switzerland, 2015)
Titanium (Ti-6Al-4V) alloy is very attractive for many applications due to its high strength-to-weight ratio and high corrosion resistance. Even then, with these attractive properties, it has poor shear strength and surface wear properties. This study is therefore undertaken to investigate the effect of sliding parameters on the surface wear behavior of Ti-6Al-4V alloy. Pin-like specimens of the alloy were produced and subjected to sliding motion on a pin-on-disk apparatus using different speeds, loads and sliding distances. The surface and specific wear rates of the alloy were evaluated as the main output of the study. Results indicate that the most severe surface wear rate of over 0.008 mm3/sec is experienced under conditions of low disk speed (50 rpm) with high input weight (46.5 N). Higher sliding distance is also found to affect the severity of the surface wear rate. All results of specific wear rates evaluated indicate that Ti-6Al-4V alloy can be classified as a low surface wear resistance material when operated under sliding counterface.